THE RELEVANCE OF ISLAMIC EDUCATION VALUES IN THE NOVEL “PROMISE” BY TERE LIYE (CASE STUDY OF PONDOK PESANTREN MAHASINA DARUL QUR'AN WAL HADITH) - Rohimah, Rohimah; Azzahra, Alifa Hani (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
Students today need alternatives to rekindle Islamic values and education. Fostering Islamic values and education is not only carried out through formal educational institutions but can also be done through printed media such as literary works like novels. This research focuses on using novels as a learning medium in the context of Islamic educational values. The researcher chose the novel "Janji" because it contains numerous Islamic educational values embedded in the characters' dialogues and narratives. "Janji" by Tere Liye, rich in Islamic educational values, offers deep insights into Islamic principles that can be applied in daily life. Therefore, the researcher connects it with the relevance to students at Pondok Pesantren Mahasina Darul Qur'an Wal Hadits. The objectives of this research are: (1) To identify the Islamic educational values present in the novel "Janji" by Tere Liye; (2) To understand the depiction of Islamic educational values in the novel "Janji" by Tere Liye and their relevance to students at Pondok Pesantren Mahasina Darul Qur'an Wal Hadits. The data collection techniques used in this research are interviews and documentation. The chosen data analysis technique is qualitative descriptive analysis. The research findings based on the Islamic educational values in the novel "Janji" by Tere Liye include: firstly, the values of Aqidah, which cover faith in Allah, faith in angels, faith in the holy books, faith in prophets and messengers, faith in the Day of Judgment, and faith in divine decree and predestination; secondly, the values of worship; and thirdly, the values of morality, which include praiseworthy and blameworthy morals. These values also align with the relevance to the students at Pondok Pesantren Mahasina Darul Qur'an Wal Hadits